Social media and its intersections with free speech, freedom of information and privacy. An analysis - Segado-Boj, Francisco; Díaz-Campo, Jesús (La Revista Icono 14, 2020)
Nowadays, there is a growing debate on the impact of social media on society, particularly on its potential negative effects. Therefore, this research is focused on three intersections of social media and fundamental freedoms: free speech, freedom of information and privacy. We begin analyzing social networking sites and social media role and evolution since their birth at the beginning of 21st century and remarking their positive aspects. Our objective is to identify malpractices related to social media and fundamental freedoms. A review of the literature is presented which outlines those malpractices. This review highlights some issues, such as arbitrary censorship, boundaries of free speech, misinformation, diversity of sources, visions and views, user content and privacy settings, and data profiling. Finally, we propose some solutions for each one of those issues.